A educação matemática no PROEJA : da concepção à sala de aula - Paiva Júnior, Francisco Pessoa de (2023)
The present Thesis has as research context the National Program for Integration of Professional Education to High School in the Mode of Youth and Adult Education - PROEJA, of the Federal Institute of Maranhão - IFMA Campus Santa Inês. This program began at the IFMA Campus Santa Inês in 2008 and continues with continuous training in the area of Administration, focused on the axis of Management and Business. In this sense, the general objective of the research is to carry out an analysis between the discourse present in the conception of the PPC of the PROEJA Administration course, and the discourses of teachers who teach mathematics, and who are determinant in their pedagogical practices. This objective arises from the research's guiding question: What are the concepts that underlie the PROEJA implemented at the IFMA Campus Santa Inês and its consonance or dissonance with the teaching of mathematics that is developed in the classroom, during the course? The main theoretical contributions that were used are: Paiva (2005, 2006, 2012), Freire (1967, 2011, 2021), Oliveira (199), Oliveira, Pinto and Ferreira (2012), Ponte (1992) and Fonseca (2020). The research was carried out in the years 2021 and 2022 and 15 subjects participated in it, 10 of them teachers and the other 5 course coordinators. For its development, we opted for the qualitative approach, endorsed in the case study by Creswell (2014), with the discursive semiotic analysis, based on Greimas (1973, 1979), Fiorin (2018, 2019), Barros (2011) and Leite (2014). ), of four data production instruments, seeking the recurrence of data between them: a) The PPC of the Technical Course in Administration in the PROEJA modality of the IFMA Campus Santa Inês; b) Semi-structured interviews with 04 PROEJA teachers at IFMA Campus Santa Inês. c) Observations on the pedagogical practices of mathematics teachers d) Electronic questionnaires applied to 05 Course Coordinators and 06 PROEJA teachers from IFMA. In this way, we conclude that the existence of dissonances between the discourses of teachers who teach mathematics and the conception present in the PPC of PROEJA/CSI reflected in pedagogical practices, imply a training that is not consistent with the needs of the public for which they are intended.